Potensi Daun Tempuyung (Sochus arvensis L) Sebagai Antihiperurisemia pada Mencit Putih Jantan - Nur Fahma Laili; Lisa Savitri (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Hyperuricemia condition occurs due to the excessive synthesis of kidney failure to eliminate uric acid. Hyperuricemia if allowed to continue will lead to chronic disorders such as kidney, cardiovascular, and gout disorders. One of the traditional alternative medicine efforts is through herbal plants. Tempuyung leaves are thought to have the potential to reduce uric acid levels. This study aims to determine whether tempuyung leaves have the potential to reduce uric acid levels. The design of the research method was the pre-post test design with the control group using 30 test animals of male Balb/c mice. Before the mice were given the treatment of the test solution, the hyperuricemia condition was made by administering the potassium oxsonate test solution. The results showed that 70% ethanol extract solution had the potential to reduce uric acid levels at a dose of 12.8 mg / 20 BW which could provide a decrease of 64.267%. The active compounds that are thought to have activity in reducing uric acid levels are flavonoids (luteolin and apigenin) which work as inhibitors of the xanthine oxidase enzyme so that the formation of uric acid can be inhibited.